The Role of Nonprofit–Private Collaboration for Nonprofits' Organizational Resilience - Rebecca Waerder; Simon Thimmel; Benedikt Englert; Bernd Helmig (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2021)
Growing social, political, and economic uncertainties have shown that organizational resilience is becoming increasingly important for nonprofit organizations (NPOs). To ensure their long-term survival, NPOs need to respond to extreme events and adapt their services and processes. The theoretical premise of resource dependence theory assumes that interactions between an organization and its environment are crucial for the long-term adaptation to adversities. The present study investigates the contributions of nonprofit–private collaborations to organizational resilience of NPOs in light of the refugee crisis in Germany in 2015. Findings from a multiple holistic case study design indicate that collaborations of nonprofits with for-profit organizations support NPOs with stability, resources, expertise, and compassion to overcome resource-based, conceptual, and emotional challenges.
Keywords: 300; Resilience; Nonprofit–private collaboration; Refugees; Multiple case study; Resource dependence theory